Community Empowerment through Sustainable Utilisation of Mangrove Forests for the Production of Natural Dyes with an Environmentally Friendly System (Phase I: Increasing Awareness and Knowledge Enhancement) - Dwi Tyaningsih Adriyanti; Tri Winarni Soenarto Putri; Aswati Mindaryani; Agus Prasetya; Himawan Tri Bayu Murti Petrus (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Community participation in mangrove forest ecosystem conservation is an effort to overcome and avoid mangrove ecosystem deterioration. The findings show that mangrove forests in Kampung Laut’s coastal region, particularly in the village of Ujung Alang, are still well preserved due to diverse mangrove planting efforts. Currently, the community uses mangrove plants by converting some plant sections into food and using the plant’s stems as building materials. Efforts have been made to preserve mangrove forest ecosystems through the Sustainable Utilisation of Mangrove Forests for the Production of Natural Dyes with a Zero Waste System. The following are the activities: 1) Dissemination of the concept to raise public awareness of the potential of mangrove plants as a source of raw materials for natural dyes to increase community income and sustainably manage mangrove forests, 2) Raising the awareness of the younger generation to improve the local economy through the development of micro-scale SMEs in the field of mangrove-based natural dyes, and 3) Technical training on thinning/logging and sustainable mangrove planting to acquaint participants with the concepts of thinning/logging and sustainable man Establish the program’s purpose, which should be divided into six activities. Many farmer groups anticipate that this community service under the auspices of Krida Wana Lestari will assist them in improving their existing products and estimating the potential process of their natural mangroves. This program raises public awareness of the mangrove plant’s potential as a source of raw materials for natural colours. In addition, this activity enables the community to do technical logging and sustainable mangrove planting to support the availability of raw materials for natural dyes. Consequently, the creation and development of a local economic business unit with a green entrepreneurship incubator model based on mangrove conservation and zero waste from natural dye SMEs have begun.